Satellite imagery as an aid to flood zone mapping - Mansor, S. B.; Ghazali, A. H.; Hashim, M. B. (1989)
Many river basins in Malaysia are frequently affected by floods, which caused an average loss of about US$40 million annually. A number of measures, structural and non-structural, were adopted recently in an effort to reduce the flood damages. One of the methods involves developing flood risk maps which will be used in flood plain management. Traditionally, flood zone mapping is a long and tedious process. As an effort to reduce the time and cost of mapping, techniques utilizing satellite images were developed. SPOT-1 multispectral data of the study area were processed using an image processing system. Bathymetric information of the study area were derived from the satellite imagery based on radiative transfer model. The flood zone boundaries is then plotted on the topographic map based on the computed of water surface profiles. The completed flood risk map enables the planners to properly plan the development of a river basin in a more economical way.